Ethnobotanical Study of Traditional Salads in Jatisampurna District, West Java, and Their Cultural and Biological Relevance - Silalahi, Marina; Septia Wahyuningtyas, Riska; Kalima, Titi; Nainggolan, Candani Shintya; Fikriyya, Nabela (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2026)
Traditional salads are diverse dishes that vary across ethnic groups and are commonly served with peanut sauce or bumbu kacang. However, local knowledge related to traditional food preparation is declining due to modernization. This study aimed to explore the diversity, types, plant composition, and preparation processes of traditional salads in Jatisampurna District, West Java. An ethnobotanical approach was employed through surveys, semi-structured interviews, and participatory observations. Five types of traditional salads were identified, namely gado-gado, pecel, karedok, asinan sayur, and rujak buni. A total of 37 plant species belonging to 31 genera and 18 families were used by traditional salad traders. The Relative Frequency of Citation (RFC) ranged from 0.2 to 1.0, while the Use Value (UV) ranged from 0.5 to 5.0. The plants used were predominantly herbs (64%), followed by trees (31%) and shrubs (5%). The preparation process was relatively similar across all salad types and could be grouped into six stages: washing and cutting ingredients; boiling, frying, or grinding; arranging ingredients in the trading cart; grinding and preparing spices; mixing spices with vegetables; and serving. Antidesma bunius, Leucaena leucocephala, and Sesbania grandiflora have significant potential for food diversification due to their nutritional value. Processing methods, especially boiling, steaming, and frying, may affect the nutritional quality of vegetables, hhighlighting the importance of optimizing processing time. Local knowledge in preparing traditional salads plays an important role in preserving biodiversity and Indonesia’s culinary heritage. Studi Etnobotani Tanaman Salad Tradisional yang Digunakan di Kabupaten Jatisampurna, Jawa Barat, Indonesia untuk Menekankan Relevansi Budaya ABSTRAK: Salad tradisional merupakan hidangan yang beragam dan bervariasi di berbagai kelompok etnis, umumnya disajikan dengan saus kacang atau bumbu kacang. Namun, pengetahuan lokal terkait pengolahan pangan tradisional mengalami penurunan akibat pengaruh modernisasi. Penelitian ini bertujuan untuk mengeksplorasi keragaman, jenis, komposisi tumbuhan, dan proses pembuatan salad tradisional di Kecamatan Jatisampurna, Jawa Barat. Penelitian ini menggunakan pendekatan etnobotani melalui survei, wawancara semi-terstruktur, dan observasi partisipatif. Lima jenis salad tradisional berhasil diidentifikasi, yaitu gado-gado, pecel, karedok, asinan sayur, dan rujak buni. Sebanyak 37 spesies tumbuhan yang termasuk dalam 31 genus dan 18 famili digunakan oleh pedagang salad tradisional. Nilai Relative Frequency of Citation (RFC) berkisar antara 0,2 hingga 1,0, sedangkan Use Value (UV) berkisar antara 0,5 hingga 5,0. Tumbuhan yang digunakan didominasi oleh herba (64%), diikuti oleh pohon (31%) dan semak (5%). Proses pembuatan salad tradisional relatif serupa pada semua jenis salad dan dapat dikelompokkan menjadi enam tahap, yaitu mencuci dan memotong bahan; merebus, menggoreng, atau menggiling; menyusun bahan di gerobak dagang; menggiling dan menyiapkan bumbu; mencampur bumbu dengan sayuran; dan menyajikan. Antidesma bunius, Leucaena leucocephala, dan Sesbania grandiflora memiliki potensi penting untuk diversifikasi pangan karena nilai gizinya. Metode pengolahan, terutama perebusan, pengukusan, dan penggorengan, berpotensi memengaruhi kualitas gizi sayuran sehingga optimalisasi waktu pengolahan menjadi penting. Pengetahuan lokal dalam pembuatan salad tradisional berperan penting dalam pelestarian biodiversitas dan warisan kuliner Indonesia.